2017
DOI: 10.1200/jco.2017.35.15_suppl.8013
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of ixazomib for relapsed/refractory multiple myeloma patients refractory to a bortezomib or carfilzomib-containing combination therapy.

Abstract: 8013 Background: The proteasome inhibitor (PI) ixazomib (Ixz) is the first orally administered PI approved for treating multiple myeloma (MM). It has shown clinical activity as a single agent and when used in other combinations. In this phase 1/2 trial, we evaluated Ixz as a replacement therapy for bortezomib or carfilzomib for MM patients who were refractory to a bortezomib- or carfilzomib-containing combination regimen. Methods: This was a phase 1/2, intra-patient, multicenter, open-label trial evaluating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Less is known about the therapeutic efficacy of ixazomib for patients who are bortezomib resistant; however, preclinical experiments point toward activity of ixazomib on cells from patients resistant to bortezomib, 31 and several studies have shown activity even in bortezomib refractory patients, 14 , 32 although responses may be infrequent. 33 , 34 Response and survival rates in this trial were lower than in a study of bortezomib/pomalidomide/dexamethasone, 35 possibly reflecting the modest response rate for bortezomib-refractory patients. Other possible approaches include optimizing the dose and schedule of the ixazomib, especially for bortezomib-refractory patients.…”
Section: Discussionmentioning
confidence: 67%
“…Less is known about the therapeutic efficacy of ixazomib for patients who are bortezomib resistant; however, preclinical experiments point toward activity of ixazomib on cells from patients resistant to bortezomib, 31 and several studies have shown activity even in bortezomib refractory patients, 14 , 32 although responses may be infrequent. 33 , 34 Response and survival rates in this trial were lower than in a study of bortezomib/pomalidomide/dexamethasone, 35 possibly reflecting the modest response rate for bortezomib-refractory patients. Other possible approaches include optimizing the dose and schedule of the ixazomib, especially for bortezomib-refractory patients.…”
Section: Discussionmentioning
confidence: 67%
“…In an experimental in vivo model, ixazomib showed activity on cells from bortezomib resistant patients 24 . This observation has been corroborated in several clinical trials; however, the variability in response observed across studies, and the small-scale study designs preclude any definite conclusions 25,26 . Responses observed in this study were comparable to bortezomib-bendamustine-dexamethasone which resulted in ORR of 60.8% in RRMM that included patients with prior exposure, but not refractory to bortezomib 11 .…”
Section: Discussionmentioning
confidence: 70%
“…Less is known about the therapeutic efficacy of ixazomib for patients who are bortezomib resistant; however, preclinical experiments point toward activity of ixazomib on cells from patients resistant to bortezomib, 31 and several studies have shown activity even in bortezomib refractory patients, 14, 32 although responses may be infrequent. 33, 34 Response and survival rates in this trial were lower than in a study of bortezomib/pomalidomide/dexamethasone, 35 possibly reflecting the modest response rate for bortezomib-refractory patients. Other possible approaches include optimizing the dose and schedule of the ixazomib, especially for bortezomib-refractory patients.…”
Section: Discussionmentioning
confidence: 67%